SISTEM INFORMASI PELAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DESA BERBASIS WEB - Siti Sufaidah; Muhyiddin Zainul Arifin; Mochammad Chumaidi (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2018)
Revenue and Expenditure Budget Village or abbreviated to APBDes every year among all the village's equipment is always busy with the utilization or management of village revenues to be allocated to several activities that aim to build the village. The main obstacles in APBDes management are lack of reporttransparency, inefficient performance, inadequate reporting thus hampering the implementation of rural development. As a form of effort to overcome this problem, it is necessary to design software application reports realization of web-based village budget usage. APBDes realization information system is web-based, using PHP web programming language and MySQL database. In implementing this system, it must be implemented or uploaded on the web server to be accessible on the internet. Because this implementation isexperimental, the author uses the XAMPP application as his web server. With the presence of these systems, the public can get information about APBDes easily without having to come to the village hall or ask for the explanation to the village apparatus and Government at the kecamatan level can also control and evaluate the reporting of APBDes relaisaasi online. So the transparency of realization of APBDes can be realized and able to answer people's doubts about the village apparatus and monitor the progress and development of their village.Keywords:APBDes, Information System, Website, Reporting, Village Finance